Mengungkap Potensi Platelet-Rich Plasma untuk Meningkatkan Kualitas Hidup Pasien dengan Nyeri Punggung Bawah: Sebuah Tinjauan Literatur - Muhammad Gagas Sasongko; Dwiky Ananda Ramadhan; Jeffry Luwito; Jonathan Latumahina; Himawan Widyatmiko; Andro Pramana Witarto (Fakultas Kedokteran Universitas Trisakti, 2026)
Low back pain (LBP) is a widespread condition that affects millions of people worldwide, causing significant limitations in daily activities and work. LBP imposes a significant economic burden through healthcare costs and lost productivity. This review explores platelet-rich plasma (PRP) therapy, a promising treatment because of its ability to regenerate tissues. We applied MeSH keywords and Boolean operators to search across multiple databases for relevant studies published in the last 10 years, including those with various study designs. PRP contains growth factors that stimulate cell activity and collagen production, which can significantly reduce pain and enhance mobility and quality of life for LBP sufferers. PRP's capacity to aid tissue repair and reduce inflammation suggests it could be beneficial for these various conditions. Compelling clinical studies have demonstrated that PRP can dramatically reduce pain and disability, offering patients renewed hope and improved outcomes. Additionally, PRP therapy is minimally invasive with rare and mild side effects, underscoring its safety and efficacy. This review underscores the urgent need for further research to refine PRP treatment protocols and confirm long-term benefits. Large-scale randomized controlled trials are essential for developing standardized guidelines and ensuring consistent, positive results across diverse patient populations. PRP therapy represents a revolutionary approach to managing LBP, promising to address the root causes and deliver lasting relief rather than merely masking symptoms. The future of LBP treatment could be significantly improved through the widespread adoption of PRP therapy.